Environmental science - Miller, Tyler G. (Brooks Cole, 2008)
If you have little or no science background, the book provides you with a solid grounding in the basics that will help you better understand environmental science concepts. Case studies--on topics ranging from the importance of insects to the reintroduction of wolves in Yellowstone Park to the world of nanotechnology--illustrate key topics and issues that affect your life. These cases inspire How Would You Vote? questions, which sharpen your critical thinking by asking you to consider facts, conflicting solutions, and trade-offs surrounding the issues, and then cast your vote